Crafting a Gender Disparity Index to Unveiling the Tea Garden Workers’ Gender Dynamics - Khalkho, Rekha; Ghosh, Souvik (Indian Journal of Extension Education, 2023)
Gender dynamics significantly impact tea garden workers’ performance. A Gender Disparity Index (GDI) was developed to assess gender differences within the tea plantation sector during 2022-23. The construction of GDI commenced with item analysis, employing the Likert’s Technique. A total of seven dimensions were included following the Harvard analytical and Moser frameworks of gender analysis. Based on the relevancy, t statistics, and content validity, five dimensions were kept in the index, namely, activity profile, influencing factors for differential roles, gender role identification, gender need assessment, and decision-making behaviour of tea garden workers. A universe of 92 items under five dimensions was prepared, and the relevancy of each item was judged by 56 experts; subsequently, 72 items were screened on which the responses of 60 workers of non-sampled tea gardens were obtained and finally 68 items were selected under five dimensions of the index followed by testing of their content validity and reliability of the index. This GDI may be used as an effective instrument to unravel gender disparities in tea gardens and other similar plantations’ estates.